BH3 mimetics antagonizing restricted prosurvival Bcl-2 proteins represent another class of selective immune modulatory drugs - Carrington, Emma M. (National Academy of Sciences, 2010)
Death by apoptosis shapes tissue homeostasis. Apoptotic mechanisms are so universal that harnessing them for tailored immune intervention would seem challenging; however, the range and different expression levels of pro- and anti-apoptotic molecules among tissues offer hope that targeting only a subset of such molecules may be therapeutically useful. We examined the effects of the drug ABT-737, a mimetic of the killer BH3 domain of the Bcl-2 family of proteins that induces apoptosis by antagonizing Bcl-2, Bcl-X(L), and Bcl-W (but not Mcl-1 and A1), on the mouse immune system. Treatment with ABT-737 reduced the numbers of selected lymphocyte and dendritic cell subpopulations, most markedly in lymph nodes. It inhibited the persistence of memory B cells, the establishment of newly arising bone marrow plasma cells, and the induction of a cytotoxic T cell response. Preexisting plasma cells and germinal centers were unaffected. Notably, ABT-737 was sufficiently immunomodulatory to allow long-term survival of pancreatic allografts, reversing established diabetes in this model. These results provide an insight into the selective mechanisms of immune cell survival and how this selectivity avails a different strategy for immune modulation.